Emerging functional similarities and divergences between Drosophila Spargel/dPGC-1 and mammalian PGC-1 protein - Mukherjee, Subhas; Basar, Mohammed A.; Davis, Claudette; Duttaroy, Atanu (Frontiers in Genetics, 2014)
Peroxisome Proliferator Activated Receptor Gamma Co-activator-1 (PGC-1) is a well- conserved protein among all chordates. Entire Drosophila species subgroup carries a PGC-1 homolog in their genome called spargel/dPGC-1 showing very little divergence. Recent studies have reported that significant functional similarities are shared between vertebrate and invertebrate PGC-1’s based on their role in mitochondrial functions and biogenesis, gluconeogenesis, and most likely in transcription and RNA processing. With the help of genetic epistasis analysis, we established that Drosophila Spargel/dPGC-1 affects cell growth process as a terminal effector in the Insulin-TOR signaling pathway. The association between Spargel and Insulin signaling could also explain its role in the aging process. Here we provided a further comparison between Spargel/dPGC-1 and PGC-1 focusing on nuclear localization, oxidative stress resistance and a possible role of Spargel/dPGC-1 in oogenesis reminiscing the role of Spargel in reproductive aging like many Insulin signaling partners. This led us to hypothesize that the discovery of newer biological functions in Drosophila Spargel/dPGC-1 will pave the way to uncover novel functional equivalents in mammals.